Persamaan dan Nuansa Perbedaan Antara Corak Peradilan Tata Usaha Negara Perancis, Belanda dan Indonesia - Khumarga, Dahnial (LAW REVIEW, 2001)
If we divide the global system of law just into two great Systems, namely Anglo American Law System and Roman Germanic Law System - not including the Islamic Law System and the Socialist law System - then Indonesia supposed to be included into the latter. This has happened because it was the Dutch colonial regime who introduce the Continental European legal system to the Netherlands East Indies some 150 years ago, while the Netherlands belonged to the Roman Germanic Law system country. Â Because of the annexation by France in the early 19 th century, the Dutch legal system it self was very much influenced by the French legal frame work, which respectively derived it from the Roman Law System. This had happened not only to the Civil and Commercial Law since the early 14 th century, but later also the Administrative Law including the Administrative Courts procedure. As far as Administrative Courts Rules are concerned, the influence of the French system to Indonesia has not just been of historical matter. The advancement and superiority of the French Administrative Courts Regulations had motivated the Indonesian as well as the Dutch government and scholars to make (comparison) studies in France with the possibility to adopt and adapt the France system into their Administrative Courts system. Nevertheless, it doesnt mean that the Dutch as well as the Indonesian Administrative Courts Rules are just a copy of the French one.Â